Efficacy of Thromboprophylaxis in Preventing Thrombotic Events in Pediatric Patients With COVID-19 or Multisystem Inflammatory Syndrome: A Systematic Review - Castillo, Jaqueline L; Medel Sánchez, Andrea; Miranda Lugo, Danna M; Núñez Muratalla, Natalia; Agredano Chávez, Cristina P; Cervantes Carrillo, Juan M; Martínez Sánchez, Gabriela V; Rios Torres, Mildred; Aguilar García, Karina; Rubio Alfaro, Lilia; Montelongo Quevedo, Mauricio; Flores Valdés, Jose R (Curēus (Palo Alto, CA), 2025)
The COVID-19 pandemic has been associated with a broad spectrum of clinical manifestations, including multisystem inflammatory syndrome in children (MIS-C), a rare but serious condition characterized by a proinflammatory and hypercoagulable state. MIS-C has been linked to an elevated risk of venous thromboembolism (VTE), necessitating a focus on thromboprophylaxis to prevent potentially fatal complications in pediatric patients. This systematic review aims to evaluate the association between COVID-19/MIS-C and thromboembolism and to assess the efficacy of thromboprophylaxis protocols in reducing thrombotic events and mortality in children. A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Literature searches were performed in PubMed, Cochrane, and Science Direct databases. Randomized controlled trials, cohort studies, and case-control studies reporting on thromboprophylaxis, thrombotic events, and associated outcomes in pediatric patients (<21 years) with COVID-19 and/or MIS-C were included. The Newcastle-Ottawa Scale was used to assess the quality of included studies. Primary outcomes were the incidence of thrombotic events and mortality, while secondary outcomes included bleeding events, clinical recovery, and changes in coagulation markers. Of the 375 articles identified, three studies (n=771 patients) met the inclusion criteria. Thromboprophylaxis protocols primarily included low molecular weight heparin (LMWH) such as enoxaparin and antiplatelet agents such as aspirin, with varied doses and treatment durations. Thrombotic events were reported in 3.3% of patients, with a higher incidence in MIS-C cases compared to COVID-19 alone. Prophylactic anticoagulation was effective in preventing thrombotic events in high-risk patients without increasing the risk of major bleeding. The studies emphasized individualized treatment approaches based on risk factors such as elevated D-dimer levels, obesity, prolonged immobilization, and central venous catheter presence. All studies reported a low mortality rate, ranging from 0% to 2.2%, highlighting the potential benefit of thromboprophylaxis in this population. Pediatric patients with MIS-C or severe COVID-19 are at an increased risk of thrombotic complications due to their heightened proinflammatory and hypercoagulable states. Thromboprophylaxis using enoxaparin and aspirin appears effective in reducing thrombotic events and mortality in these patients. Individualized protocols based on clinical risk factors and D-dimer levels are critical to optimizing outcomes while minimizing bleeding risks. Standardized, evidence-based guidelines are needed to refine thromboprophylaxis strategies and determine the optimal duration of therapy in this vulnerable population. Further research is essential to better understand the role of coagulation markers in guiding treatment cessation and improving outcomes.